2021
DOI: 10.3390/polym13203521
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Soft Core/Hard Shell Ratios on the Coating Performance of Acrylic Copolymer Latexes

Abstract: Core–shell acrylic copolymer latexes containing bio resourced itaconic acid with different compositions in respect with the core and shell segments were synthesized, characterized, and applied as coating materials for leather. The purpose of the study was to evidence the high coating performance of the latexes when the ratio of the core/shell differed from 90/10 to 50/50 wt %. The copolymers were prepared via emulsion copolymerization technique and the products were isolated and characterized by means of struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Based on ATR-FTIR spectroscopy, it is possible to analyze the surface of polymer films and obtain structural information about the composition of the matrix or structural changes. [38,42,43] The solvent-treated polymer films were pressed onto the ATR crystal with a stamp and measured at points of interest, as well as at points that showed no abnormalities. Solvent residues and changes in the chemical structure of the matrix or in the environment of the samples can be detected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on ATR-FTIR spectroscopy, it is possible to analyze the surface of polymer films and obtain structural information about the composition of the matrix or structural changes. [38,42,43] The solvent-treated polymer films were pressed onto the ATR crystal with a stamp and measured at points of interest, as well as at points that showed no abnormalities. Solvent residues and changes in the chemical structure of the matrix or in the environment of the samples can be detected.…”
Section: Methodsmentioning
confidence: 99%
“…As PDMS has a hydrophobic surface, highly polar solvents such as water or ethanol are suitable for PDMS microfluidic systems due to their low solubility, while less polar solvents and amines such as hexamine or triethylamine are used to remove oligomers from PDMS. [36][37][38] As the dielectric membrane has direct contact with the solvent in the manufacturing processes of the DET electrodes, an interaction is expected. The nature of the solvent can thus have a significant impact on the type and intensity of this interaction.…”
mentioning
confidence: 99%
“…Composite latex particles have been of great interest in the last decade due to their technology that allows us to create particle morphologies, giving us the possibility to combine different polymer properties [ 18 , 19 , 20 , 21 , 22 ]. This kind of particle morphology is often called as core-shell achieved by multi-stage emulsion polymerization, where a monomer composition is polymerized to form a core and another monomer composition is post-polymerized over the core-seed to form the shell.…”
Section: Introductionmentioning
confidence: 99%
“…Ma summarized three growth mechanisms of core–shell latex particles: graft polymerization, interpenetrating network polymerization, and ionic bonding. By conducting a series of synthesis experiments, Qian and Yilmaz demonstrated that the structural stability of the core–shell emulsion is determined by the polarity and thermodynamic property of the polymer components, which guides the particle design and rheological improvement of core–shell emulsions. In recent years, acrylate, epoxy, polyurethane, aniline resin, and siloxane have been used in the synthesis of core–shell emulsions.…”
Section: Introductionmentioning
confidence: 99%